Diversity of endophytic fungal species from Styrax benzoin found in benzoin-producing locations in North Sumatra. Issue 1 (November 2021) - Slamet, W Y; Faulina, S A; Hidayat, A; Susilowati, A; Elfiati, D; Rahayu, L M; Turjaman, M
Abstract: Styrax benzoin is a native tree to Indonesia, particularly in North Sumatra. This plant species produces benzoin resin, which is beneficial for medicinal treatments, hence its commercial value. Endophytic fungi help produce bioactive metabolites and contribute to resin production. However, the diversity of endophytic fungal species from S. benzoin grown in North Sumatra remained largely unexplored. This study aims to determine the distribution and diversity of culturable endophytic fungi from two kemenyan -producing locations in North Sumatra, Simalungun and North Tapanuli, as well as their tree part origin. A total of 7 and 8 endophytic fungal species were obtained from barks, stems, and/or leaves of S. benzoin grown in Simalungun and North Tapanuli, respectively, and identified by internal transcribed spacer sequence analysis. Endophytic fungi from North Tapanuli showed higher diversity, with a Shannon-Wiener index of 2.31 than those from Simalungun (1.95). Morisita-Horn similarity indices for bark-stem, stem-leaf, and bark-leaf were 0.47, 0.08, and 0, respectively, hinting at organ-specificity colonization. This study offers insights into the diversity of endophytic fungi isolated from S. benzoin which may contribute to future improvement of benzoin resin production.